2017
DOI: 10.1007/s00401-017-1694-x
|View full text |Cite
|
Sign up to set email alerts
|

IRE1 signaling exacerbates Alzheimer’s disease pathogenesis

Abstract: Altered proteostasis is a salient feature of Alzheimer's disease (AD), highlighting the occurrence of endoplasmic reticulum (ER) stress and abnormal protein aggregation. ER stress triggers the activation of the unfolded protein response (UPR), a signaling pathway that enforces adaptive programs to sustain proteostasis or eliminate terminally damaged cells. IRE1 is an ER-located kinase and endoribonuclease that operates as a major stress transducer, mediating both adaptive and proapoptotic programs under ER str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
167
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(178 citation statements)
references
References 103 publications
8
167
1
2
Order By: Relevance
“…The heightened level of ER stress and downstream responses in AD‐affected regions has been confirmed by both in vivo and in vitro evidence (Remondelli & Renna, 2017). Conditional deletion of Ire1 , a key component of the UPR, directly results in reduced cognitive impairment in rodent neurodegenerative models, which further confirms the promotive role by ER stress toward AD progression (Duran‐Aniotz, Cornejo, Espinoza, Ardiles, & Medinas, 2017) (Table 2). At present, while the initiation of ER stress in susceptible neurons remains unclear, genetic alterations, age‐related functional insufficiency, oxidative stress, or secondary to proteotoxic damage are assumed to be possible causes, which eventually lead to the impaired chaperone, calcium imbalance, and ER stress (Cai, Arikkath, Yang, Guo, & Periyasamy, 2016).…”
Section: The Important Role Of Protein Synthesis Pathways In Cancer Asupporting
confidence: 59%
“…The heightened level of ER stress and downstream responses in AD‐affected regions has been confirmed by both in vivo and in vitro evidence (Remondelli & Renna, 2017). Conditional deletion of Ire1 , a key component of the UPR, directly results in reduced cognitive impairment in rodent neurodegenerative models, which further confirms the promotive role by ER stress toward AD progression (Duran‐Aniotz, Cornejo, Espinoza, Ardiles, & Medinas, 2017) (Table 2). At present, while the initiation of ER stress in susceptible neurons remains unclear, genetic alterations, age‐related functional insufficiency, oxidative stress, or secondary to proteotoxic damage are assumed to be possible causes, which eventually lead to the impaired chaperone, calcium imbalance, and ER stress (Cai, Arikkath, Yang, Guo, & Periyasamy, 2016).…”
Section: The Important Role Of Protein Synthesis Pathways In Cancer Asupporting
confidence: 59%
“…Remarkably, genome wide screening to identify XBP1s-target genes uncovered a cluster of genes related to AD [47] and an etiological genetic association between XBP1 promoter polymorphism and AD increased risk development was revealed in the Chinese population [48]. Consistent with this we recently reported that XBP1 expression directly impacts APP metabolism [43]. A recent study indicated that delivering the active form of XBP1 into the hippocampus of AD mice restored synaptic function [50].…”
Section: Gene4c Muta4onsmentioning
confidence: 53%
“…Consistent with this, brain samples from AD patients presented augmented XBP1 [41]. XBP1 mRNA splicing is also observed after amyloid β treatment in neuronal cell lines [45] and in the temporal cortex of AD patients [43,46]. Remarkably, genome wide screening to identify XBP1s-target genes uncovered a cluster of genes related to AD [47] and an etiological genetic association between XBP1 promoter polymorphism and AD increased risk development was revealed in the Chinese population [48].…”
Section: Gene4c Muta4onsmentioning
confidence: 68%
See 1 more Smart Citation
“…Specifically, his group demonstrated that a brain-conditional knockdown of Xbp1 can also improve pathology in murine models of age-related diseases such as amyotrophic lateral sclerosis (ALS) and Huntington's disease (HD). He also showed that IRE1 deficiency protects against Alzheimer's disease (Duran-Aniotz et al, 2017), and discussed the development of gene therapy strategies to attenuate ER stress in disease.…”
Section: Modulation Of Protein Aggregation -Age and Other Factorsmentioning
confidence: 99%